Healthy plant-based diet index as a determinant of bone mineral density in osteoporotic postmenopausal women: A case-control study - Ghadiri, Marzieh; Cheshmazar, Elhameh; Shateri, Zainab; Gerami, Shirin; Nouri, Mehran; Gargari, Bahram Pourghassem (Frontiers in Nutrition, 2023)
Introduction: The association between plant-based diet indices and bone mineral density (BMD) of women with osteoporosis have not been studied in Iranian women. This study aimed to evaluate the association between plant-based diet indices and BMD in postmenopausal women with osteopenia/osteoporosis. Method: The present research was a case-control study conducted on 131 postmenopausal women with osteoporosis/osteopenia and 131 healthy. The BMD of the femoral neck and lumbar vertebrae was measured by the Dual-energy X-ray absorptiometry (DXEA) method. Participants were asked to complete a validated semi-quantitative food frequency questionnaire (FFQ). We used three versions of plant-based diet indices, including plant-based diet index (PDI), healthy plant-based diet index (hPDI), and unhealthy plant-based diet index (uPDI). Two different multivariable logistic regression was used for the crude and adjusted model to assess the relationship between PDI, hPDI, and uPDI with odds of femoral and lumbar BMD. Results: There was a reverse association between last tertile of hPDI with femoral BMD abnormality in the both adjusted model (Model 1: odds ratio (OR): 0.33; 95% confidence interval (CI): 0.19-0.63 and Model 2: OR: 0.30; 95% CI: 0.15-0.58, respectively). Furthermore, we found a reverse relationship between hPDI with lumbar BMD abnormality in the first adjusted model (OR: 0.36; 95% CI: 0.19-0.67). On the other hand, a negative association was observed in the second and last tertile of hPDI with lumbar BMD abnormality (OR: 0.47; 95% CI: 0.24-0.90 and OR: 0.34; 95% CI: 0.17-0.64, respectively). According to the results, the association of femoral BMD abnormality in the last tertile of uPDI compared to the first tertile in the both adjusted models (Model 1: OR: 2.85; 95% CI: 1.52-5.36 and Model 2: OR: 2.63; 95% CI: 1.37-5.06) were significant. Also, we observed a positive relationship between the last tertile of uPDI with lumbar BMD abnormality compared to the lowest tertile in the both adjusted models (Model 1; OR: 4.16; 95% CI: 2.20-7.85, Model 2; OR: 4.23; 95% CI: 2.19-8.19). Conclusion: Overall, the findings indicated that in postmenopausal women with osteoporosis, a healthy plant-based diet could prevent bone loss, and an unhealthy plant-based diet might have detrimental effects on BMD.